2018
DOI: 10.1111/tbed.13096
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of myelocytomatosis caused by mutational avian leukosis virus subgroup J in China, 2018

Abstract: Avian leukosis virus subgroup J (ALV‐J) was isolated in meat‐type breeder chickens for the first time in 1988 in the United Kingdom. Due to the application of an eradication program, there were fewer reports related to myelocytomatosis or ALV‐J in China after 2013. However, there was another breakout almost simultaneously in six provinces of China in February 2018. On‐site, 15‐ to 20‐week‐old broiler breeder chickens showed depression, paralysis and weight loss. Mortality for certain flocks reached 15%. Sick c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 14 publications
1
31
0
Order By: Relevance
“…Since early 2018, typical AL has re‐emerged in white‐feathered broilers in several provinces of China, and the daily mortality of those farms ranged with the mortality in affected farms ranging from 1/10,000 to 19/10,000 per day. Although a previous study has showed that in Shandong and Hebei, the outbreak of ALV was caused by a mutated strain of ALV‐J, mainly inducing myelocytomatosis in 15‐ to 20‐week‐old Ross broiler breeder chickens (Zhou et al, ), we noticed that there exist differences in pathogenic characteristics between different chicken farms, which drove us to conduct a wider epidemiological survey.…”
Section: Discussionmentioning
confidence: 81%
“…Since early 2018, typical AL has re‐emerged in white‐feathered broilers in several provinces of China, and the daily mortality of those farms ranged with the mortality in affected farms ranging from 1/10,000 to 19/10,000 per day. Although a previous study has showed that in Shandong and Hebei, the outbreak of ALV was caused by a mutated strain of ALV‐J, mainly inducing myelocytomatosis in 15‐ to 20‐week‐old Ross broiler breeder chickens (Zhou et al, ), we noticed that there exist differences in pathogenic characteristics between different chicken farms, which drove us to conduct a wider epidemiological survey.…”
Section: Discussionmentioning
confidence: 81%
“…ALV-J infection currently causes great economic losses in China [17], and it presence is associated with a variety of tumour types including myeloma, renal tumours and hemangioma [19,32]. The high incidence of tumours reduces production, and virus elimination increases production costs.…”
Section: Discussionmentioning
confidence: 99%
“…even spread to waterfowl and wild birds [16]. Most large foreign breeder companies had eradicated classic exogenous ALVs by the end of the 1980s, but ALV-J remains widespread in China [17].…”
mentioning
confidence: 99%
“…Attributed to the implementation of ALV-J eradication program (6), there were rarely reports of ALV-J or myelocytomatosis in China after 2013. Nevertheless, there were another intensive reports about ALV-J breakout almost simultaneously in six provinces of China in 2018, which attracted our attention (7). It is rather remarkable that there were extensive medullary-like tumor cells in the bone marrow, liver, and kidney, and all of the neoplasms were myelocytomas (7).…”
Section: Introductionmentioning
confidence: 95%